MECCIAS trial: Metabolic consequences of continuous veno-venous hemofiltration on indirect calorimetry. Issue 12 (December 2020) - Jonckheer, J.; Demol, J.; Lanckmans, K.; Malbrain, M.L.N.G.; Spapen, H.; De Waele, E.
Summary: Background: and aims: Caloric prescription based on resting energy expenditure (REE) measured with indirect calorimetry (IC) improves outcome and is the gold standard in nutritional therapy of critically ill patients. Until now continuous renal replacement therapy (CRRT) precluded the use of IC due to several mechanisms. We investigated the impact of CRRT on V̇CO2, V̇O2 and REE to facilitate indirect calorimetry during CRRT. Methods: In 10 critically ill ventilated patient in need of continuous veno-venous hemofiltration (CVVH) using citrate predilution we performed IC in 4 different states: baseline, high dose, baseline with NaCl predilution and without CVVH. CO2 content of effluent fluid was measured by a point of care blood gas analyzer. Carbon dioxide production (V̇CO2 ) measured with IC was adapted by adding the CO2 flow of effluent and deducing CO2 flow in postdilution fluid to calculate a true V̇CO2. True REE was calculated with the Weir equation using the true V̇CO2 . Results: CO2 removal in effluent during baseline, high dose and NaCl predilution was respectively 24 mL/min, 38 mL/min and 23 mL/min. Together with the CO2 delivery by the postdilution fluid this led to an adaptation of REE respectively by 34 kcal/d or 2% (p = 0, 002), 44 kcal/d or 3% (p = 0, 002) and 33 kcal/d or 2% (p = 0, 002). Compared to the true REE during baseline of 1935 ± 921 kcal/d, true REE during high dose was 1723 ± 752 kcal/d (p = 0.65), during NaCl predilution it was 1604 ± 633 kcal/d (p = 0.014) and without CRRT it was 1713 ± 704 kcal/d (p = 0.193). Conclusions: CO2 alterations due to CVVH are clinically of no importance so no correction factor of REE is needed with or without CVVH. IC must be performed during CVVH as CVVH seems to alter metabolism. These changes may be mainly explained by the use of citrate predilution. Highlights: When REE is measured with IC, CO2 alterations due to CVVH are clinically of no importance. IC must be performed during CVVH as CVVH seems to alter metabolism. These changes may be mainly explained by the use of citrate predilution.